Vertigo Due to Vascular Mechanisms - Kim, Hyun Ah; Lee, Hyung; Kim, Ji-Soo (Seminars in Neurology, 2020)
Isolated dizziness and vertigo due to vascular mechanisms are frequently misdiagnosed as peripheral vestibulopathy or vestibular migraine. For diagnosis of strokes presenting with an acute prolonged (≥ 24 hours) vestibular syndrome, findings on clinical examination, such as HINTS (negative head impulse tests, detection of direction-changing gaze-evoked nystagmus, and presence of skew deviation), are more sensitive than findings on neuroimaging. Since HINTS alone cannot securely detect anterior inferior cerebellar artery strokes, additional attention should be paid to the patients with unexplained hearing loss in addition to acute prolonged vestibulopathy. For diagnosis of transient (< 24 hours) spontaneous vestibular syndrome due to vascular mechanisms, the presence of associated craniocervical pain and focal neurological symptoms/signs is the clue. Even without these symptoms or signs, however, vascular imaging combined with perfusion- and diffusion-weighted MRI should be performed in patients with multiple vascular risk factors or a high ABCD2 score (age, blood pressure, clinical features, duration of symptom, and presence of diabetes).
Keywords: dizziness; vertigo; stroke; infarction